Pancasila Sebagai Landasan Pembentukan Hukum Adat dalam Konteks Negara Hukum Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Lukluil Maxnuun; Fatimah Nur Laily; Muthiah Prima Zahra (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Pancasila, as the foundation of the Indonesian state, plays a crucial role in the formation of law, including customary law. This research focuses on how Pancasila’s values serve as a basis for the recognition and development of customary law, which is still acknowledged within the national legal system. The urgency of this study lies in finding a common ground between national law and customary law to strengthen a just rule of law. The research method used is a normative approach, analyzing legislation and legal literature. The results indicate that Pancasila can function as a foundation for harmonizing customary law and national law, thus reinforcing Indonesia’s plural legal identity. The conclusion is that Pancasila, as the state’s foundational philosophy, provides space for the existence of customary law, as long as it aligns with the core values of Pancasila.